2006
DOI: 10.1093/scan/nsl012
|View full text |Cite
|
Sign up to set email alerts
|

Imitating expressions: emotion-specific neural substrates in facial mimicry

Abstract: Intentionally adopting a discrete emotional facial expression can modulate the subjective feelings corresponding to that emotion; however, the underlying neural mechanism is poorly understood. We therefore used functional brain imaging (functional magnetic resonance imaging) to examine brain activity during intentional mimicry of emotional and non-emotional facial expressions and relate regional responses to the magnitude of expression-induced facial movement. Eighteen healthy subjects were scanned while imita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
119
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(141 citation statements)
references
References 74 publications
19
119
2
1
Order By: Relevance
“…First, it has been reported that a patient with Foix-Chavany-Marie syndrome, a form of pseudo bulbar palsy resulting from bilateral opercular lesions, was unable to yawn voluntarily (whether spared involuntary yawning was spontaneous and/or contagious is unclear; Laurent-Vannier, Fadda, Laigle, Dusser, & Leroy-Malherbe, 1999). Second, and more convincingly, recent f MRI investigations of mouth movements have shown that very proximal, if not the same, regions of the pIFG in BA44 are activated when participants are asked to smile (Warren et al, 2006), imitate facial expressions (Lee, Josephs, Dolan, & Critchley, 2006;van der Gaag, Minderaa, & Keysers, 2007), manipulate small objects with their lips , listen to pure mouth sounds (e.g., crunching a piece of candy with the teeth, kissing, gurgling, crunching potato chips, finishing a can of soft drink with a straw; Gazzola et al, 2006), or listen to nonverbal human vocalizations (Warren et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…First, it has been reported that a patient with Foix-Chavany-Marie syndrome, a form of pseudo bulbar palsy resulting from bilateral opercular lesions, was unable to yawn voluntarily (whether spared involuntary yawning was spontaneous and/or contagious is unclear; Laurent-Vannier, Fadda, Laigle, Dusser, & Leroy-Malherbe, 1999). Second, and more convincingly, recent f MRI investigations of mouth movements have shown that very proximal, if not the same, regions of the pIFG in BA44 are activated when participants are asked to smile (Warren et al, 2006), imitate facial expressions (Lee, Josephs, Dolan, & Critchley, 2006;van der Gaag, Minderaa, & Keysers, 2007), manipulate small objects with their lips , listen to pure mouth sounds (e.g., crunching a piece of candy with the teeth, kissing, gurgling, crunching potato chips, finishing a can of soft drink with a straw; Gazzola et al, 2006), or listen to nonverbal human vocalizations (Warren et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Inferior prefrontal hemodynamic activity previously has been shown to increase with the amount of explicit imitation that a person exerts (e.g., using a facial imitation task; Lee et al, 2006), and more recently, this region has been shown to become active when unconscious word yawning does not always occur every time a yawn stimulus has been perceived. Although some yawn stimuli are more effective than others, a stimulus that is effective for one person may not be so for another.…”
Section: Pifg Neurons: Triggers For Contagious Behavior?mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the general view that the IFC is linked to several first-order executive processes, such as stimulus comparisons or the judgment of stimuli (Petrides, 2005), it might specifically serve several self-referenced or other-referenced social processes, such as the evaluation (Marumo et al, 2009), categorization (Frühholz et al, 2009, and memory encoding of emotional stimuli (Sergerie et al, 2005). The IFC might also be involved in controlling, overriding, or inhibiting behavioral and emotional responses (Aron et al, 2004;Dillon and Pizzagalli, 2007;Mitchell, 2011), as well as mirroring (Leslie et al, 2004), empathizing (Schulte-Ruther et al, 2007), or imitating the behavior of other individuals (Lee et al, 2006). All of these socially relevant processes can be regarded as first-order executive processes.…”
Section: A General Functional Role Of the Ifcmentioning
confidence: 99%
“…Therefore a mismatch between the gestures planned and simulated for oneself (or the person seen from a first-person perspective) and the gestures simulated for the interaction partner might afford additional processing. This conflict hypothesis would therefore predict an enhanced involvement of brain areas related to conflict processing and negative effect including lateral orbitofrontal cortex (lOFC), anterior cingulate cortex (ACC) involved in detection of conflict, and dorsolateral prefrontal cortex (DLPFC) engaged to resolve the conflict 5 in the antimimicry condition (Buchel, Morris, Dolan & Friston, 1998;Carter & van Veen, 2007;Lee, Dolan & Critchley, 2008;Lee, Josephs, Dolan, & Critchley, 2006;O'Doherty et al, 2001;Small et al, 2001). …”
Section: Introductionmentioning
confidence: 99%